Veterinary Pharmaceutics: An Opportunity for Interprofessional Education in New Zealand? - Arlene McDowell; Rebekah Beard; Anna Brightmore; Lisa W. Lu; Amelia McKay; Maadhuri Mistry; Kate Owen; Emma Swan; Jessica Young (MDPI AG, 2017)
Globally pharmacists are becoming increasingly involved in veterinary medicine; however, little is known about the level of interest for pharmacists playing a larger role in animal treatment in New Zealand. A key stakeholder in any progression of pharmacists becoming more involved in the practice of veterinary pharmacy is the veterinary profession. The aim of this study was to investigate views of veterinarians and veterinary students on the role of pharmacists supporting veterinarians with advice on animal medicines. Open interviews were conducted with veterinarians in Dunedin, New Zealand. Veterinary students at Massey University completed an online survey. Most veterinarians do not have regular communication with pharmacists regarding animal care, but believe it may be beneficial. In order to support veterinarians, pharmacists would need further education in veterinary medicine. Veterinary students believe there is opportunity for collaboration between professions provided that pharmacists have a better working knowledge of animal treatment. Most of the veterinary students surveyed perceive a gap in their knowledge concerning animal medicines, specifically pharmacology and compounding. While there is support for pharmacists contributing to veterinary medicine, particularly in the area of pharmaceutics, this is currently limited in New Zealand due to a lack of specialized education opportunities.